Relationship Between Pre- and Post-exercise Body Mass Changes and Pre-exercise Urine Color in Female Athletes - Rebecca M. Lopez; Dallin C. Lund; Amanda J. Tritsch; Victoria Liebl (Frontiers in Sports and Active Living, 2022)
Although studies use body mass changes or urine color to measure hydration status, the purpose of this study was to examine the relationship between pre-practice urine color and exercise body mass changes in female tackle football players. Twenty-six female American football players (Age: 29.9 ± 7.3 years; Height: 165.2 ± 2.6 cm; Weight: 83.8 ± 24.4 kg) volunteered. Fluid consumptions (FC) was measured during tackle football practices, while urine color (Ucol), and percent body mass loss (%BML) were taken before and after practices. Subjects were grouped by %BML: lost mass (LM), gained mass (GM), or no change (NC). A one-way ANOVA compared groups on Ucol and FC. There were differences across groups for pre-practice Ucol (P < 0.01) and FC (P < 0.01). GM had a higher pre-practice Ucol than LM (P < 0.01) and NC (P < 0.05) and consumed more fluid than LM (P < 0.01) and NC (P < 0.05). A stepwise linear regression examined the extent that Ucol and FC were related to %BML. When predicting BML, FC accounted for 45% of variance (P < 0.01). The addition of pre-practice Ucol increased predicted variance explained (R2 change= 2.5%, P = 0032). Subjects who gained mass during practice arrived with elevated urine color (Ucol 5 ± 2), while those who lost mass arrived with pale urine color (Ucol 3 ± 2). Findings indicate those who arrived with an elevated urine color attempted to improve hydration status by consuming more fluid and gaining body mass during exercise.